2011
DOI: 10.1111/j.1559-1816.2011.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Organizational Obstruction and the Expanded Model of Organizational Identification

Abstract: We argue that perceptions of organizational support and obstruction will have unique implications for employees' cognitive association and disassociation with their employers. As expected, the results of 2 studies support the hypothesis that perceived organizational support is positively related to an overlap in individual and organizational identities (i.e., organizational identification). Further, perceptions of organizational obstruction predict cognitive separation in individual and organizational identiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(86 citation statements)
references
References 56 publications
(101 reference statements)
3
77
0
6
Order By: Relevance
“…To understand the "symbolic" effects of psychological contracts, Restubog et al (2008) argued-and found support for-the proposal that organizational identification and organizational trust mediated the relationship between psychological contract breach and organizational citizenship behavior. Other correlational studies by Kreiner and Ashforth (2004) and Gibney et al (2011) demonstrate negative relationships between breach and organizational identification.…”
Section: Psychological Contracts and Social Identitymentioning
confidence: 91%
See 2 more Smart Citations
“…To understand the "symbolic" effects of psychological contracts, Restubog et al (2008) argued-and found support for-the proposal that organizational identification and organizational trust mediated the relationship between psychological contract breach and organizational citizenship behavior. Other correlational studies by Kreiner and Ashforth (2004) and Gibney et al (2011) demonstrate negative relationships between breach and organizational identification.…”
Section: Psychological Contracts and Social Identitymentioning
confidence: 91%
“…In other words, an employee could take a disinterested stance towards the organization in which he or she does not identify nor disidentify with the organization (Bhattacharya and Elsbach 2002). Second, confirmatory factor analysis by Kreiner and Ashforth (2004) demonstrate that organizational identification and organizational disidentification are related but discrete constructs and that the two constructs have different antecedents (see also Gibney et al 2011).…”
Section: Psychological Contracts and Social Identitymentioning
confidence: 96%
See 1 more Smart Citation
“…In a study of gender minorities in higher education, Steele et al (2002) found that women in majors dominated by men experienced higher levels of social identity threats than other students and were more likely to think about changing their major as compared to others. Relatedly, Gibney et al (2011) found that when employees perceive that their organization obstructs their goal fulfilment, they tend to disidentify with the organization.…”
Section: Interest and Self-efficacymentioning
confidence: 99%
“…Finally, future research may also want to include an organizational identification measure, since it tends to be reduced by perceived organizational obstructions (Gibney et al 2011). Perhaps women who are reminded of the vertical gender segregation in academia identify less with their university, while a gender-equality prime increases identification.…”
Section: Limitationsmentioning
confidence: 99%